Analysis of Sports Interest Among Sports Science Students of Makassar State University Class 2022-2023: Questionnaire Approach And Its Implications - Faiz Faiz; Muhammad Imam Fauzi; Syarif Hidayatullah; muhammad Arief Setiawan (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study aims to analyze the factors influencing the sports participation interest among students of the Sports Science Department at Universitas Negeri Makassar for the 2022-2023 academic year. The research utilizes a quantitative approach with a descriptive method, aimed at providing an objective picture of students' interest in physical activity. The data was collected using a closed-ended questionnaire distributed to 100 students, with a Likert scale used to measure attitudes and perceptions regarding their involvement in sports. The results revealed that the majority of students were aware of the importance of exercise for physical and mental health, with 90% acknowledging its significance. However, only 40% of the respondents reported being highly motivated to exercise consistently. The study found that social support from family and friends played a key role in encouraging students to engage in sports. On the other hand, barriers such as inadequate sports facilities on campus, time constraints due to academic schedules, and financial limitations were identified as significant obstacles. Despite these challenges, 85% of students recognized the psychological benefits of exercise, including stress reduction and increased productivity. Based on these findings, the study recommends improving campus sports facilities, offering structured sports programs, providing financial support for sports participation, and increasing awareness of the psychological benefits of physical activity. The findings provide valuable insights for universities to develop policies that promote a more active lifestyle among students, particularly those in the field of sports science.